Gang phantasmagoria: how racialized gang allegations haunt immigration legal work - Muñiz, Ana (Critical criminology, 2022)
Through an analysis of interviews with Southern California attorneys, supplemented by archival materials, this article contributes to the literature on gangs, critical criminology, and Gothic tropes by examining how the ambiguous nature of gang profiling allows state actors to target racialized others in various legal and administrative venues with little evidence and few procedural protections. I conceptualize gang phantasmagoria as the constant, amorphous, unpredictable, and haunting threat of racialized gang allegations and argue that the dynamic shapes the work of legal practitioners and constitutes a state mechanism of racial terror. Specifically, first I argue that government officials deploy the specter of gangs to both portray asylum seekers as monstrous threats and justify restrictions in asylum eligibility. I then illustrate how the potential for gang phantasmagoria to upend asylum applications and trigger the deportation of their clients elicits constant low-grade anxiety for attorneys. Consequently, attorneys are forced to adopt more cautious approaches to legal work in a way that indirectly facilitates the social control of young Latinx immigrants.